Paediatric bilateral thalamic glioma: Case report and literature review (2019)
1. Introduction Primary thalamic tumours are rare [1]. They account for 1–1.5% of all brain tumours and approximately a quarter of them occur in children younger than 15 years [2,3]. Bilateral thalamic gliomas (BTGs) are extremely rare sub-types of thalamic tumours, which are known to have a poor outcome regardless of the treatment modality [4]. About 70 cases have been reported so far in the literature [5]. We present the outcome of treatment of BTG in a three-year-old Nigerian child and a brief review of the literature on these uncommon types of central nervous system tumours. 2. Case Presentation A three-year-old right-handed boy presented with headache, abnormal gait, and inability to sit unsupported of one week duration. There was an associated history of drowsiness, excessive sleeping, and multiple episodes of projectile vomiting. Examination revealed a young boy who was fully conscious but drowsy. His pupils were of normal size but reacted sluggishly to light. He had bilateral abducens nerve palsies, bilateral papilloedema, global hypertonia/hyperreflexia, and bilateral extensor plantar responses. He also had truncal ataxia and dysmetria but no sensorimotor deficit. Examination of other systems revealed normal findings. A clinical diagnosis of acute onset raised intracranial pressure from an infratentorial space-occupying lesion was made. Cranial computed tomography scan showed bilateral symmetrical enlarged thalamic nuclei which were hypodense to isodense and non-contrast enhancing (Fig. 1a and b). There was associated obstructive hydrocephalus. Brain magnetic resonance imaging showed bilateral symmetrical non-enhancing masses involving both thalami (with estimated volumes of 40.17 cm³ on the right and 44.84 cm³ on the left). These were hypointense on T1-weighted images and hyperintense on T2-weighted and FLAIR images. There was associated dilatation of the lateral ventricles and effacement of the quadrigeminal/ambient cisterns bilaterally (Fig. 2a–d). A radiological diagnosis of a bilateral thalamic tumour was made. The patient's management was multidisciplinary, involving the neurological surgery, radiology, pathology, paediatric oncology, and radiation oncology teams. A biopsy specimen obtained via an endoscopic transventricular route showed features of a WHO grade II diffuse astrocytoma (Fig. 3a–c). He subsequently received sixteen courses of Vincristine/Carboplatin chemotherapy, which was later changed to Etoposide/Cisplatin on account of clinico-radiological evidence of tumour progression. He had cerebrospinal fluid diversion (via a ventriculoperitoneal shunt) five months after the initial procedure due to worsening hydrocephalus (Fig. 4a–c). The second-line chemotherapeutic agents were discontinued after the third cycle on request by the patient's mother because of their side effects (bone marrow suppression, widespread dermatitis, recurrent chest infection). Radiotherapy was considered unsafe in this patient given his age and the potential for radiation-induced neurocognitive decline (on the advice of the radiation oncology team). Repeat neuroimaging at six months following the initial surgery showed further tumour progression with involvement of the caudate nuclei and brainstem, and extension into the lateral ventricles (Fig. 5a–c). Attempts at switching his chemotherapeutic agents were futile due to non-availability of the drugs. At nine months post tumour biopsy, he had recurrent headache and vomiting, expressive aphasia, worsening gait imbalance, ataxia, paraparesis, bilateral ptosis, upgaze paresis, and choreoform movements. He subsequently defaulted follow-up.